Sosialisasi tentang Penyakit Hipertensi pada Masyarakat di Desa Seruawan Kecamatan Kairatu Kabupaten Seram Bagian Barat - Windarti Rumaolat; Idham Soamole; Ratnasari Rumakey; Syariefah Hidayati Waliulu (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Hypertension is often referred to as a “silent killer” because it generally develops without clear symptoms, despite posing serious risks to public health. The condition affects communities in many countries, including Indonesia and Maluku Province, highlighting the need for continuous health promotion and preventive interventions. This community outreach initiative was conducted in Seruawan Village, Kairatu District, with the aim of improving residents’ knowledge, increasing awareness, and encouraging behavioral changes related to hypertension prevention. The activity consisted of three main stages: preparation, implementation, and evaluation. A total of 37 residents participated actively and enthusiastically throughout the program. Educational materials covered hypertension risk factors, early detection, healthy lifestyles, and preventive practices. Evaluation results showed a substantial increase in participants’ knowledge. Before the educational session, only 16.2% of residents demonstrated a good level of understanding, whereas after the intervention, this proportion increased to 81.1%. These findings indicate that structured health education effectively strengthens community understanding and supports sustainable preventive behavior against hypertension.